Zebra pattern in rocks as a function of grain growth affected by second-phase particles - Kelka, Ulrich; Koehn, Daniel; Beaudoin, Nicolas (Frontiers in Physics, 2015)
Alternating fine grained dark and coarse grained light layers in rocks are often termed zebra patterns and are found worldwide. The crystals in the different bands have an almost identical chemical composition, however second-phase particles (e.g., fluid filled pores or a second mineral phase) are concentrated in the dark layers. Even though this pattern is very common and has been studied widely, the initial stage of the pattern formation remains controversial. In this communication we present a simple microdynamic model which can explain the beginning of the zebra pattern formation. The two dimensional model consists of two main processes, mineral replacement along a reaction front, and grain boundary migration affected by impurities. In the numerical model we assume that an initial distribution of second-phase particles is present due to sedimentary layering. The reaction front percolates the model and redistributes second-phase particles by shifting them until the front is saturated and drops the particles again. This produces and enhances initial layering. Grain growth is hindered in layers with high second-phase particle concentrations whereas layers with low concentrations coarsen. Due to the grain growth activity in layers with low second-phase particle concentrations these impurities are collected at grain boundaries and the crystals become very clean. Therefore, the white layers in the pattern contain large grains with low concentration of second-phase particles, whereas the dark layers contain small grains with a large second-phase particle concentration. The presence of the zebra pattern is characteristic for regions containing Pb-Zn mineralization. Therefore, the origin of the structure is presumably related to the mineralization process and might be used as a marker for ore exploration. A complete understanding of the formation of this pattern will contribute to a more accurate understanding of hydrothermal systems that build up economic mineralization.